The Effect Fear of Missing Out (FoMO) from Generation Z in Medan to Cancel Culture and herd mentality (Mob Mentality) as the Social Control for Public Figure - Muhammad Arief; Dewi Kurniawati; Rahmanita Ginting (Komunika, 2025)
This research entitled about The Effect Fear Of Missing Out (Fomo) From Generation Z In Medan To Cancel Culture And Herd Mentality (Mob Mentality) As The Social Control For Public Figure. A Quantitative study that aims to analyze Fear of missing out from gen z in Medan whether having the effect to cancel culture as the social control for public figure, to analyze fear of missing out from gen z in Medan whether having the effect to herd mentality (mob mentality) as the social control for public figure, and to analyze fear of missing out from gen z in Medan whether hving the effect to cancel culture and herd mentality (mob mentality as the social control public figure. This research took place in two subdistricts in Medan, that are Medan Area Subdistrict and Medan Selayang Subdistrict. Medan Area Subdistrict has 119.029 populations and Medan Selayang Subdistricts has 109.926 population. This research uses cluster random sampling as the sampling techinique. The results are 52 samples represent for Medan Area Subdistrict and 48 samples represent form Medan Selayang Subdistrict. The result of this research indicates that the correlation between fear of missing out and cancel culture is obtained for r=0,884 and p=0.000 (p<0.09) therefore H01 is being rejected and Ha1 is being accepted in addtion to the standart of significant variable. The correlation between fear of missing out and herd mentality (mob mentality)is obtained from r=0.822 and p=0,000 (p<0,05) therefore Ho2 is being rejected and Ha2 is being accepted in addition to the standart variable of significant = 0,01.